2011
DOI: 10.3945/jn.110.128215
|View full text |Cite|
|
Sign up to set email alerts
|

Growth to Age 18 Months Following Prenatal Supplementation with Docosahexaenoic Acid Differs by Maternal Gravidity in Mexico

Abstract: Little is known about the long-term effects of DHA intake during pregnancy. Offspring of primagravid Mexican women who received 400 mg/d DHA from wk 20 of gestation through delivery were heavier and had larger head circumferences at birth than children whose mothers received placebo; no effect was observed in offspring of multigravidae. We have followed these children (n = 739; 76% of the birth cohort), measuring length, weight, and head circumference at 1, 3, 6, 9, 12, and 18 mo. At 18 mo, intent-to-treat dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
0
33
0
3
Order By: Relevance
“…In the Viva study, a lower prevalence of obesity was found at 3 years in children whose mothers had a higher fi sh intake during pregnancy (and a better ω 3 status at birth), whereas in a preceding publication, a lower birth weight for gestational age was reported if mothers had a high fi sh intake in pregnancy [15,38] . In the Mexican study, 18-month-old children of primigravid mothers who had received DHA supplements in pregnancy were longer but not slimmer, although at birth, they were observed to have a higher weight and head circumference [43,46] . Clearly, the settings were different in all these studies, as well as population background, habitual diets, supplementation, and observation periods; even the sources, compositions, and doses of the supplements varied greatly.…”
Section: Discussionmentioning
confidence: 96%
“…In the Viva study, a lower prevalence of obesity was found at 3 years in children whose mothers had a higher fi sh intake during pregnancy (and a better ω 3 status at birth), whereas in a preceding publication, a lower birth weight for gestational age was reported if mothers had a high fi sh intake in pregnancy [15,38] . In the Mexican study, 18-month-old children of primigravid mothers who had received DHA supplements in pregnancy were longer but not slimmer, although at birth, they were observed to have a higher weight and head circumference [43,46] . Clearly, the settings were different in all these studies, as well as population background, habitual diets, supplementation, and observation periods; even the sources, compositions, and doses of the supplements varied greatly.…”
Section: Discussionmentioning
confidence: 96%
“… EAA that cannot be synthesised by mother and fetus are histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, tryptophan, and valine; amino acids that are inadequately synthesised by gestating mother and her fetus include arginine and glutamine; NEAA that can be synthesised presumably in adequate amounts by mother and fetus include alanine, asparagine, aspartate, cysteine, glutamate, glycine, proline, serine, taurine, and tyrosine 28,29 …”
Section: Nutritional Needs For Fetal Growth and Developmentmentioning
confidence: 99%
“…Niños de madres que fueron suplementadas con omega 3 durante el embarazo, presentaron mayor coordinación y memoria comparados con niños de madres sin suplementar ante pruebas de habilidades cognitivas (memoria y coordinación) (26). Un estudio en niños mexicanos demostró que los hijos de madres primerizas suplementadas con 400 mg/día de DHA a las 20 semanas de gestación tuvieron neonatos más grandes y con mayor circunferencia de cabeza que las madres no suplementadas (27). También se ha demostrado que el consumo de estos ácidos grasos tiene efectos benéfi cos en funciones motoras y de aprendizaje, mejora de la agudeza visual, así como la prevención de alergias y enfermedades autoinmunes.…”
Section: Omegaunclassified